Human epithelial-type ovarian tumour marker beta-2-microglobulin is regulated by the TGF-β signaling pathway. Issue 1 (December 2016) - Sun, Wenwen; Gui, Lu; Zuo, Xulei; Zhang, Lingyun; Zhou, Daibing; Duan, Xiaoling; Ren, Weimin; Xu, Guoxiong
Abstract Background Beta-2-microglobulin (B2M), a light chain subunit of the major histocompatibility complex (MHC) class I complex, has been implicated in tumorigenesis. However, whether it is expressed in different epithelial-type ovarian tumours remains unknown. This study was performed to examine the expression of B2M in different histopathological types of ovarian tumours, to explore the function of B2M in ovarian cancer (OC) cells and to investigate the mechanisms underlying the regulation of B2M by the TGF-β signaling pathway. Methods B2M expression in normal ovarian tissues and epithelia-type ovarian tumours was detected by immunohistochemistry and Western blot, followed by the analysis of association with clinical features. OC cells were transfected with B2M-siRNA and cell proliferation, migration and invasion were determined by WST-1 assay, wound healing assay and Transwell invasion assay, respectively. The regulation of B2M by the TGF-β signaling pathway in OC cells was examined by Western blot, ELISA and qRT-PCR. Results We found that B2M was overexpressed in ovarian borderline and malignant tumours compared with benign tumours and normal controls, but was not associated with age, tumour size, lymph node metastasis and clinical stage. Knocking down of B2M led to a decrease in OC cell proliferation, migration and invasion. The expression of B2M was downregulated by TGF-β1 in OC cells, which was abolished in the presence of the inhibitor of TGF-β type I receptor. Conclusion Our findings suggest that B2M is a potential tissue biomarker and therapeutic target of borderline and malignant ovarian tumours and the dysregulation of B2M in these tumours may be mediated by the TGF-β signaling pathway.